Tri-Band Slot-Loaded Microstrip Antenna for Internet of Things Applications - Refaat, S. Mohamed; Abdalaziz, A.; Hamad, E. K. I. (Advanced Electromagnetics, 2021)
A new design of a multiband microstrip patch antenna using slots in the patch as well as defected ground structures (DGS) implemented in the ground plane is proposed. Multi resonance response was obtained by etching the DGS shapes in the ground plane of a Traditional patch operates at 5.2 GHz, which is the common frequency for the Internet of Things (IoT) applications. The novel outcome of this work is a compact antenna that resonates at three bands, viz. 2.42, 5.22 and 5.92 GHz. Different shapes of slots were used to improve the antenna performance at the different resonances. The antenna used the inset feeding technique to improve impedance matching. Rogers RO3003 substrate of 3 relative dielectric constant, 0.0013 loss tangent, and 1.5 mm thickness was used to build the antenna. The designed antenna was simulated using HFSS software. The good consistency between simulations and measurements confirmed the antenna's ability to improve the benefits for IoT applications at the three different frequencies.